ANALISIS KETIDAKBERHASILAN PROGRAM PEMBIAYAAN USAHA SYARIAH (PUSYAR) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT KOTA MOJOKERTO - Pratiwi, Finna Dewi; Widiastuti, Tika (al-Uqud : Journal of Islamic Economics, 2017)
The background on this research that there are many people who have not managed a prosperous but has received funding from the program pusyar in Mojokerto. It thus indicates that the program pusyar conducted in Mojokerto experiencing the failure. The purpose of this study was to analyze the failure of programs to improve the welfare pusyar. The method used is a qualitative exploratory methods. The primary data obtained from interviews, observation and documentation of the parties associated with programs such as the SRB pusyar, Baznas, MES and also people who have not managed to prosper. While secondary data in this study were obtained from the print media or internet about pusyar, supporting data from a variety of journals, books that are relevant to the research. The results of the analysis carried out indicates that there are six factors to failure program pusyar in improving the well-being, namely: the level of income of the people that there is no improvement, the length of the process undertaken by the pusyar, funds provided to large businesses more than for small businesses, a guarantee that burden the people , the absence of assistance and facilities of the parties pusyar, and MES is not performing its role to the fullest.